Implementasi Kolak Tahu untuk Meningkatkan Prestasi SD Negeri Bakalan 01 - Mirmanto, Nurman (Jurnal Penelitian Multidisiplin Ilmu, 2025)
This research was conducted at SD Negeri Bakalan 01 as a form of learning leadership analysis conducted by the principal. The implementation of Kolak Tahu is able to provide changes to the culture of quality, active collaboration, organized, humanist and the progress of school achievement, especially SD Negeri Bakalan 01. The success of the school and students is not only one principal's personnel but active collaboration carried out by the principal, teachers, students, parents' association, and related stakeholders who inspire each other. The consistency of the implementation of collaboration is carried out in an organized, comprehensive and sustainable manner in shaping and instilling the culture and character of humanist attitudes, namely humanizing humans. Translated with DeepL.com (free version)